HUBUNGAN ANTARA PENGUASAAN MATA DIKLAT PRODUKTIF DAN NILAI PRAKTIK KERJA INDUSTRI DENGAN HASIL UJI KOMPETENSI KEAHLIAN SISWA KELAS XII TEKNIK KENDARAAN RINGAN DI SMK NEGERI 1 GANTIWARNO KLATEN TAHUN AJARAN 2014/2015 - Andre Permana Putra; Samidjo Samidjo (Jurnal Taman Vokasi, 2016)
This research aims to know the correlation between mastery of productive training subjek and the score of industry practice with student’s skill competency result, the correlation between industry practice with student’s skill competency result, the correlation between mastery productive training subjek with skill competency result of XII class student’s of light vehicle engineering SMK Negeri 1 Gantiwarno 2014/2015.This research is an ex-post facto study. The subject was class XII student of light vehicle engineering SMK Negeri 1Gantiwarno Klaten 2014/2015 consisting 65 student. This research was population research from 65 respondent. Data collection technike of this research was documentation. Partial correlation analysis was taken to know the correlation of independent variable with dependent variable, while to know the correlation both of independent variables together to dependent variable was using multiple correlation analysis. Before analysing data, there was prerequisite test such as normality test, linierity test and multikolinearity test.The result of this research showed that there is a positive and significant correlation between mastery productive training subject with student’s skill competency result. It is proved by the score of correlation is 0,410. There is a positive and significant correlation between the score of industry pratice with student’s skill competency result. It is proved by the score of correlation is 0,199. There is a positive and significant correlation between mastery productive training subject and the score industry practice with student’s skill competency result. It is proved by the score of correlation is 0,424.